2009
DOI: 10.1097/pcc.0b013e3181a63eac
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric critical care telemedicine in rural underserved emergency departments*

Abstract: With telemedicine, it is feasible to provide urgent subspecialty critical care for children in underserved rural EDs, improve patient care, and provide a high degree of provider satisfaction. Pediatric critical care telemedicine may help to address the disparities in the access to and the outcome of medical care between rural and urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 25 publications
2
102
1
Order By: Relevance
“…Staff acceptance was the primary focus of 10 studies, 23,26,29,30,34,[36][37][38]40,41 whereas it was a secondary focus of the remaining 13. 5,21,22,24,25,27,28,[31][32][33]35,39,42 Tele-ICU Confi guration: There was signifi cant variation in how tele-ICU was defi ned, used, and structured ( Table 2 ). In 12 studies (52%), tele-ICU involved bedside monitors and cameras, 5,24,[29][30][31][32]34,[36][37][38]40,41 whereas the remaining 11 (48%) used mobile cameras or robots.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff acceptance was the primary focus of 10 studies, 23,26,29,30,34,[36][37][38]40,41 whereas it was a secondary focus of the remaining 13. 5,21,22,24,25,27,28,[31][32][33]35,39,42 Tele-ICU Confi guration: There was signifi cant variation in how tele-ICU was defi ned, used, and structured ( Table 2 ). In 12 studies (52%), tele-ICU involved bedside monitors and cameras, 5,24,[29][30][31][32]34,[36][37][38]40,41 whereas the remaining 11 (48%) used mobile cameras or robots.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In 12 studies (52%), tele-ICU involved bedside monitors and cameras, 5,24,[29][30][31][32]34,[36][37][38]40,41 whereas the remaining 11 (48%) used mobile cameras or robots. [21][22][23][25][26][27][28]33,35,39,42 Likewise, 12 (52%) studies described systems using around-the-clock telemonitoring, 5,21,24,29,30,32,34,[36][37][38]40,41 whereas seven (30%) entailed only on-call consultation, 22,23,31,33,35,39,42 and four (17%) used a system of regularly scheduled telerounds. [25][26][27][28] Thirteen (57%) studies included tele-ICUs structured on a hub-and-spoke model, 5,21,…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Lastly, this study is consistent with previous research which has demonstrated that specialty telemedicine consultations can result in improved patient safety. 18,[39][40][41][42][43][44] …”
Section: Discussionmentioning
confidence: 99%
“…3,8,11 Telemedicine is increasingly used to address some of these shortcomings by providing pediatric specialty consultations to children presenting to rural and underserved EDs as an alternative to telephone consultations. [17][18][19] Specifically, telemedicine has the potential to prevent medication errors resulting from the lack of access to experienced staff and pediatric specialty expertise. [20][21][22][23][24][25] The goal of the current study was to evaluate whether pediatric telemedicine consultations are associated with fewer physicianrelated medication errors among seriously ill and injured children presenting to rural EDs.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…4 At last count, an estimated 10% of ICU beds in the United States were covered by ICU telemedicine in the form of continuous remote monitoring, with many more using some other type of remote care. 7 Pediatric-specific uses for telemedicine in the ICU are also vast and include (1) urgent telemedicine consultations with pediatric intensivists, neonatologists, and cardiac intensivists for children in underserved rural emergency departments or ICUs lacking such expertise [8][9][10][11][12] ; (2) teleconsultations with pediatric subspecialists in infectious diseases, cardiology, and neurology for children in community hospitals without local access to these subspecialists 13 ; and (3) nighttime telecommunication between attending pediatric intensivists on home-call with fellows and residents caring for pediatric ICU patients in a teaching hospital to enhance continuity of care and augment team communication during off hours. 14 Although a wide body of research exists to explore how best to utilize telemedicine to extend the reach of a limited cadre of critical care subspecialty physicians, 15 little has been done to investigate how this technology can be used by non-physician specialists, including respiratory therapists (RTs), for whom the scope of practice is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%